ANALISA PENGELOLAAN MODAL KERJA TERHADAP TINGKAT LIKUIDITAS PADA UD. CAHAYA MANDIRI DI KOTA AMBON - Rumra Suryanti Ismail; Marissa Silooy (Soso-Q : Jurnal Manajemen, 2018)
This   study   aimed   to   analyze   the   influence   of   working   capital management to the level of liquidity in UD. Cahaya Mandiri in the city of Ambon from years 2014-2016. Variables used in this study is the management  of  working  capital  and  liquidity  as  the  independent variable as the dependent variable. Statistical methods used in this study is a simple linear regression analysis in ad vance of working capital management with measurement tools that turnover of working capital and liquidity analysis measuring devices are used, among others Curren Ratio, Quick Ratio and Cash Ratio. The result showed that the management  of  working  capital  have  a  negative  impact  and  no significant effect on the level of liquidity in the company UD. Cahaya Mandiri in the city of Ambon.Keywords: Working Capital Management, Liquidity and Ratio Analysis